PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITYSEBAGAI VARIABEL MODERASI - Kurniasih, Retno; Jaryono, Jaryono; Najmudin, Najmudin (Performance, 2012)
Researches on the influence of financial performance toward corporate value have been widely conducted and showed different results. In several researches, financial performance, which is measured by profitability ratio has a positive effect on corporate value. However there are also some findings that profitability has a negative effect. Researcher predicted that there are other influencing factors. This condition drives researcher to use Corporate Social Responsibility (CSR). The aim of this research is to examine the influence of financial performance which is measured by profitability ratio, liquidity ratio, leverage ratio, and activity ratio toward corporate value by considering Corporate Social Responsibility as moderating variables. The population of this research are corporates which have been the winner of ISRA (Indonesia Sustainability Reporting Award) and also listed on the Indonesia Stock Exchange. Hypothesis is tested by regression analysis to find out the interactive influence of the moderating variables. The corporate value is measured by Price to Book Value (PBV), while disclosure of CSR is measured by CSR Index. The results indicate that ROE, DER, TATO and the disclosure of CSR has a positive effect toward corporate value, CR has no effect toward corporate value, and the disclosure of CSR is not able to moderate relation between financial performance toward